The historical, social, and economic importance of the potato crop - Ortíz, O.; Mares, V. (Springer, 2017)
The potato has a fascinating history, from its origin and domestication in the Andean Region, where it was essential for feeding a growing population, for example, the Inca Empire, to its introduction into farming and food systems in Europe and elsewhere in the world. This crop has been the key factor in terms of food security, nutrition, population growth and urbanization in many regions. In recent decades, the potato has become a dominant crop in countries such as China and India, and its cropping area and production have increased more than those of any other food crop in Africa. Besides the social and economic importance of potato, extensively discussed in several published articles and briefly mentioned in this chapter, we discuss two relevant issues that are intimately related to potato genomics and breeding and which make potato a crop that has a lot to offer for the future. Those issues are the potato’s contribution to food and nutrition security, and the cultural and genetic importance of biodiversity conservation in the Andes; these issues are strongly related to gender, since women in traditional societies have contributed—and still contribute—to an enormous wealth of knowledge in relation to biodiversity conservation and utilization. The adaptability shown by the potato crop over thousands of years indicates the potential role of the potato as a climate-smart crop, particularly based on its short vegetative period, water utilization efficiency, and productive capacity per unit of input.